The Relationship Between Perceptions of Multicultural Competence and Democratic Values: Examining Science Teachers Working with International Students - Doğru, M. Said; Demirbaş, İbrahim (Journal of International Students, 2021)
The present study aims to determine the perceptions of multicultural competence and democratic values of science teachers in schools where international students study and to find out whether there is a relationship between them. The study surveyed 436 secondary school science teachers in the Western Black Sea region in the 2018–2019 academic year. Data were collected using the Perceptions of Multicultural Competence Scale and the Democratic Values Scale. We found positive and moderate relationship between teachers’ perceptions of multicultural competence and their democratic values. As teachers’ democratic values increased, their perceptions of multicultural competence increased, and as their democratic values decreased, their perceptions of multicultural competence decreased as well. Understanding teachers’ opinions about democratic values, justice, respect for differences, and equality reveals an important relationship between their multicultural competence and their democratic values.